The effectiveness of extracorporeal shockwave lithotripsy in treating ureteral stones: a retrospective study in Misrata- Libya (مجلة البحوث الأكاديمية, 2022)
The objective of this study was to evaluate the efficacy of extracorporeal shockwave lithotripsy in treating ureteral stones.Methods and materials: this is a retrospective study, in which we reviewed A total of 60 cases (29 males and 31 females) with ureteral stones who were treated by extracorporeal shock wave lithotripsy (ESWL) from records of ESWL unit at Misrata Medical Center between January 2019 and December 2019. All Radiopaque ureteral stones of radiological stone size of ≤ 15 mm were included in the study. Number of sessions, energy used and complications were reported. The outcome of ESWL was also recorded.Result: Of the 60 patients (29 males and 31 females) analyzed, extracorporeal shock wave lithotripsy was successful in 83.3%. Univariate analysis of both groups revealed no significant difference in patient’s age and stone laterality. Statically significant differences in gender, stone size, stone site, number of extracorporeal shock wave lithotripsy sessions, and patients with stents were observed. Statically significant factors in multivariate logistic regression analysis were sex and stent. Females had three-time higher risk for extracorporeal shock wave lithotripsy failure than male (odds ratio (OR) = 3.213; 95% confidence interval (CI): 1.194–8.645; p = 0.021) and a higher failure rate when stent was used (OR = 6.358; 95% CI: 2.228–18.143; p = 0.001). This study reveals that extracorporeal shock wave lithotripsy can treat ureteric stones successfully with an invasive association between outcome and predictors such as stone size, site and presence of stent. These factors can help us in improving patient selection and ensure better outcome at lower cost.
Keywords: ESWL; Ureteral stone; Misrata; MMC